A FIELD STUDY ON THE REASON TO CHOOSE THE PROGRAMME, MOTIVES, PREPAREDNESS TO UNIVERSITY EDUCATION AND ACADEMIC PERFORMANCE OF ACCOUNTING PROGRAMME STUDENTS - Hatunoğlu, Zeynep; Kaya, Ahmet; Angaykutluk, Filiz (International Journal of Research -GRANTHAALAYAH, 2018)
This paper examines the perceptions of first-year students (freshmen) of accounting at Akdeniz University (AU) and Kahramanmaras Sutcu Imam University (KSU) to explore a range of factors which impact on students’ learning: their motives for entering higher education, their rationale for selecting an accounting programme, their preparedness for further study and their expectations. The study also explores the influence of these antecedent variables on academic performance in the first accounting module. Data was collected from 420 accounting students in first year classes at the AU and KSU. The data required for this study was collected via a questionnaire which was developed by Byrne and Flood in 2005 known as the Motives, Expectations and Preparedness for University (MEPU) questionnaire. Results show that there is a relation between interest in accounting as professional career and accounting first grade. First semester average mark shows positively that the willingness of accounting as a career influence the grades positively. KSU students rated higher than AU students in some statements of motives for attending university, preparedness for university, reason for choosing accounting programme. It can also be said that female students and KSU students have stronger motives and higher expectations for entering higher education.